Environmental planning and the evolution of inter-basin water transfers in the United States - Yi, Sooyeon; Kondolf, G. Mathias (Frontiers in Environmental Science, 2024)
The uneven spatial distribution of water resources and demands across the US have motivated a wide range of inter-basin water transfers. By redistributing water resources, Inter-basin water transfer projects can lead to specific environmental changes such as altered river flows, changes in water quality, and loss of ecologically important habitats, impacts which depend on project scale and management. Early water transfer projects were undertaken prior to legislation Since the primary focus is not on the environmental impacts of these projects, they are often not documented historically. We provided a comprehensive inventory of inter-basin water transfer projects (built, incomplete, proposed) in the US, identified patterns of these projects’ characteristics, analyzed the growing role of environmental planning in these projects, and drew lessons to inform future proposals. We categorized historical US water transfer projects into three periods: 1900–1930, 1930–1970, and 1970–2020, analyzing projects over 40 km long and 50 MCM/year using diverse sources, to assess their development from an environmental planning perspective. Results of this study show that the early projects, mostly gravity-driven and smaller-in-scale, grow in scale and require more pumping stations (energy-intensive) to lift the water over high elevations. California and Colorado are the most active, using these transfers for the first time. Federal agencies have reduced funding for most transfers due to a growing recognition of the environmental impacts, which were not adequately addressed in planning of early projects. Environmental impacts are crucial for the planning and operation of inter-basin water transfer projects. We recommend that assessments of climate change vulnerability should also be considered essential for future project proposals.